Patterns of Religious Behavior in the Sundanese Community: Insights from Hasan Mustapa’s Work - Albustomi, Ahmad Gibson; Qomaruzzaman, Bambang (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This study fundamentally aims to comprehend the construction of religious life in the community, dissect the process of socialization or the introduction of religion within the community, and analyze the internalization of religious life from the perspective of Peter L. Berger. This study employs a qualitative approach with a descriptive-holistic method. Data are gathered through documentation and the study of texts authored by Hasan Mustapa. The data analysis method employed is literary analysis, particularly focusing on Hasan Mustapa’s work, “Sasaka Dika Islaman,” using procedures that encompass thematic identification, inclusion and exclusion criteria, structuralization, interpretation, and integration. The findings of this study reveal that: (1) The construction of religious life in the Sundanese community, as depicted in “Sasaka Dika Islaman,” reflects a reflective model of the development of individual and communal life; (2) The process of socializing religious teachings and values produces two patterns of religious behavior in individuals within the community, namely critical and apathetic religious behaviors, each with its own consequences; (3) The process of internalizing religious life gives rise to a duplicative consciousness, encompassing a social self and a non-social self, resulting in alienation. This study contributes to the academic knowledge and discourse in the fields of Religious Studies and Sociology of Religion. The analysis of Peter L. Berger’s social construct offers a fresh perspective in comprehending the religious behaviors of individuals and communities, particularly within the Sundanese community as elucidated in Hasan Mustapa’s work, “Sasaka Dika Islaman.”